Three-dimensional subsidence analysis and gravity modelling of the continental margin offshore Namibia - Stewart, J; Watts, A; Bagguley, J (2000)
Seismic reflection profiles and gravity anomaly data have been used to determine the structure and evolution of the Namibian continental margin. In comparison to other margins, the gravity anomaly at the Namibian margin shows a number of distinctive features. It lacks an offshore gravity 'low', and, despite the presence of up to 9 km of sediments, the gravity 'high' is displaced landwards of the maximum sediment thickness. In an attempt to explain these features, the Early Cretaceous-Recent stratigraphic record is analysed using a combined 3-D backstripping and gravity modelling technique that enables constraints to be placed on the long-term mechanical properties of the lithosphere. A neutral depth of necking and relatively high flexural rigidity (or equivalent elastic thickness, T(e), of ~25 km) can explain part of the anomaly, at least in the south of the margin. However, large residual anomalies exist that can be reduced by the presence of pre-rift low-density sediments within the zone of maximum stretching, south of 22°S, high-density volcanic material at the eastern pinch-out of the lower rift sequence and a lateral sediment density variation across the shelf, slope and rise. In addition, the presence of a magmatic body at the base of the crust, provided that the flexural strength of the margin is high, significantly improves the fit between observed and calculated gravity anomalies. Recovered stretching factors enable predictions of the geometry of the Moho to be made. Palaeobathymetry is estimated along the entire margin through time by comparing the subsidence determined from backstripping to that predicted by simple models of rifting. These estimates are within the errors of observed palaeowater depths where well control exists. The requirement of high T(e) rather than T(e) that increases with time suggests that stretched continental crust extends offshore for some distance and the continent-ocean boundary occurs in relatively deep water near magnetic anomaly M4. Reconstruction of the gravity field of the South Atlantic at 100 Ma illustrates that, in terms of their gravity signature, the South Atlantic margins are asymmetric.